Ectopic expression of GmNF-YA8 in Arabidopsis delays flowering via modulating the expression of gibberellic acid biosynthesis- and flowering-related genes and promotes lateral root emergence in low phosphorus conditions - Ou, Siyan; Xu, Zhihao; Mai, Cuishan; Li, Bodi; Wang, Jinxiang (Frontiers in Plant Science, 2022)
NUCLEAR FACTOR Y subunit alpha (NF-YA), together with NF-YB and NF-YC, regulates plant growth and development, as well as plant responses to biotic and abiotic stresses. Although extensive studies have examined the functions of NF-YAs in Arabidopsis thaliana, the roles of NF-YAs in soybean (Glycinme max) are poorly understood. In this study, we identified a phosphorus (P) starvation-responsive NF-YA8 in soybean. GmNF-YA8 expression was induced by low P or low nitrogen in the leaves, but not by potassium or iron starvation, respectively. GmNF-YA8 was localized to nucleus and plasma membrane. Ectopic expression of GmNF-YA8 reduced plant growth and delayed flowering in Arabidopsis. Exogenous application of gibberellic acid (GA) rescued the delayed flowering phenotype in overexpressing GmNF-YA8 Arabidopsis lines GmNF-YA8OE-05 and GmNF-YA8OE-20. Moreover, real time quantitative PCR analysis verified that overexpression of GmNF-YA8 downregulated GA20ox2 and GA3ox2 expression, but upregulated GA2ox2 and GA2ox3 that encode enzymes, which inactive bioactive GAs. Consistent with the late flowering phenotype of Arabidopsis trangenic lines that overexpress GmNF-YA8, the transcript levels of flowering-promoting genes AP1, CO, LFY, and SOC1 were reduced. In addition, overexpression of GmNF-YA8 promoted the emergence of lateral root (LR) primordia from epidermis rather than the initiation of LR in low P, and increased the LR density in low nitrogen. Our results provide insight into the roles of GmNF-YA8.